Comparing The Evidence of Liquidation Process Between Islamic Rural Banks and Conventional Rural Banks in Indonesia - Ashari, Hasan; Kustiani, Nur Aisyah; Nugrahanti, Trinandari Prasetya (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2024)
This research aims to compare the findings obtained during the liquidation process of the Islamic Rural Bank with Conventional Rural Bank. This article seeks to provide understanding for Islamic banking practitioners and regulators to improve the regulatory framework and operational practices of Islamic Rural Banks in the future. This research uses a qualitative approach focusing on cases found in the liquidation process of these banks. Data was collected through a questionnaire distributed to the Liquidation Team of Islamic Rural Banks who were assigned by the Indonesia Deposit Insurance Corporation to carry out the liquidation process and who have expertise and experience in explaining the liquidation process of Islamic Rural Banks. The main findings show causes for the liquidation of Islamic Rural Bank, such as fraud and weaknesses in governance. However, Islamic Rural Bank tend to show lower claim recovery rates upon liquidation compared to Conventional Rural Bank. Both types of banks benefit from LPS innovations which facilitate the liquidation process efficiently and quickly, resulting in relatively the same liquidation completion time.